Segmentation of talent management variables in selected public higher learning institutions - Lukman@Zawawi, Mohamad; Kamal, M.Y. (2017)
The Higher Learning Institutions (HLIs) either in abroad or local have implemented Talent Management (TM) for years and they have successfully developed the human capital. Each public HLIs have their own strategic planning to achieve mission and vision of the organization. Therefore, by having a competence staff will ensure the target will be accomplished. Therefore, it is important to identify the level of TM practices which are attracting, recruiting, developing and retaining talent in the public HLIs. This study is to examine the level of TM practices which are attracting, recruiting, developing and retaining talent in selected public HLIs. Quantitative method has been used to conduct this research in selected public HLIs which are Universiti Sains Malaysia (USM), Universiti Pendidikan Sultan Idris (UPSI) and Universiti Teknologi Mara (UiTM). In quantitative method, descriptive survey has been conducted towards 714 respondents. Further, the data collected was analyzed by using IBM Statistical Packages Social Sciences (SPSS). USM showed the highest moderate level of attracting, recruiting, developing and retaining talent as compared to UPSI and UiTM. This study revealed the significant impact of having a proper system of TM practicing in order to complete the mission and vision of the organization. Even though, the levels of TM practices were in moderate level, it shows that there are rooms for improvement and able to trigger the top management of public HLIs to improve the TM practices system.